2020
DOI: 10.1002/edm2.162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of prediabetes, and diabetes in Chandigarh and Panchkula region based on glycated haemoglobin and Indian diabetes risk score

Abstract: There is a rapid increase in the prevalence of diabetes in India. We wanted to review the status of prediabetes and diabetes in the combined population of Chandigarh and Panchkula region based on both Indian Diabetes Risk Score (IDRS) and Glycated Haemoglobin (HbA1c). A total of 1215 subjects were recruited during the screening process, out of which 444 i subjects have been analysed for the current study on the basis of high risk for IDRS (≥60) and their known diabetes status. This study included 431 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…After eliminating subjects with a history of consumption of antibiotics in the last 6–8 weeks, absence of paired duodenum/stool sample and low read sequencing depth (< 2000), 54 subjects with paired samples were finally analyzed. Based on the blood parameters; fasting plasma glucose (FPG; mg/dl), postprandial glucose (PPG; mg/dl) and glycated hemoglobin (HbA1c, %), subjects with FPG > 100 mg/dl and HbA1c ≥ 5.7%; were classified as hyperglycemic, while those with FPG ≤ 100 mg/dl and HbA1c < 5.7%; were classified as normoglycemic 58 . Overall, 33 established hyperglycemic and 21 normoglycemic were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…After eliminating subjects with a history of consumption of antibiotics in the last 6–8 weeks, absence of paired duodenum/stool sample and low read sequencing depth (< 2000), 54 subjects with paired samples were finally analyzed. Based on the blood parameters; fasting plasma glucose (FPG; mg/dl), postprandial glucose (PPG; mg/dl) and glycated hemoglobin (HbA1c, %), subjects with FPG > 100 mg/dl and HbA1c ≥ 5.7%; were classified as hyperglycemic, while those with FPG ≤ 100 mg/dl and HbA1c < 5.7%; were classified as normoglycemic 58 . Overall, 33 established hyperglycemic and 21 normoglycemic were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Ramchandran et al reported 14% prevalence of prediabetes in the Indian population (19). Further, Kumar et al also revealed the prevalence of diabetes and prediabetes in a joint population of Chandigarh & Panchkula with 12.67% and 11.69% respectively (20). Moreover, in the Asian Indian population, the risk for conversion from prediabetic to a diabetic is more vulnerable in comparison with the other ethnic population groups (21)(22).…”
Section: Discussionmentioning
confidence: 98%
“…Whether the regulatory effect of yoga on HDL is mediated through a reverse cholesterol transport mechanism [ 43 ] that includes macrophage cholesterol efflux in arteries or an antioxidant or anti-inflammatory effect [ 44 , 45 , 46 ] mediated by NO promoting activity needs to be evaluated [ 43 ]. The increased number of diabetes cases in the Indian population creates a substantial economic burden [ 47 , 48 , 49 , 50 ] and poses a threat to having age-related disorders [ 51 , 52 , 53 ]. Therefore, the study may be extrapolated to other populations based on the varied acceptability of yoga protocol as its perceived benefits, barriers, and compliance may vary from one country to another.…”
Section: Discussionmentioning
confidence: 99%